RECONSTRUCTION OF PROSTITUTION LAW IN PERSPECTIVE OF RELIGIOUS NORMS AND RENEWAL OF CRIMINAL LAW - Noor Fajari Rofiq (Universitas Muhammadiyah Malang, 2020)
Cases of prostitution as the subject of commercial sex workers (Pekerja Sex Komersial) and sex service users until now are free to undergo without the threat of punishment. Until now, there has been no rule that can punish prostitutes or prostitutes and their customers .then there needs to be a legal reconstruction to achieve a responsive law then need to reform the law to achieve the law in the goal. This research aimed to know and understand the Construction of Prostitution Crimes in the Criminal Code, and The Penal Code Bill is associated with Religious Norms. And Know and understand the Construction of Formulation of Prostitution Crimes that are Ideal and in line with religious norms for Indonesian society, as for normative juridical research methods. The approach used in this writing is a statutory approach or (statute approach) and the analytical and conceptual approach analysis of legal concepts. The results show that it is necessary to explore the concept of philosophical, sociological, and juridical basic values that the state to have legal certainty in society in the Criminal War draft stage. So digging into the philosophical value of the 1st Pancasila, The One Godhead (Ketuhanan yang Maha Esa), the five religions apply in Indonesia, including Islam, Christianity, Catholicism, Hindu, Buddha, and Confucian has asserted that the practice of prostitution is legally prohibited.